Arsenic species in mesopelagic organisms and their fate during aquafeed processing. (September 2022) - Tibon, Jojo; Amlund, Heidi; Gomez-Delgado, Ana I.; Berntssen, Marc H.G.; Silva, Marta S.; Wiech, Martin; Sloth, Jens J.; Sele, Veronika
Abstract: A responsible harvest of mesopelagic species as aquafeed ingredients has the potential to address the United Nations Sustainable Development Goal 14, which calls for sustainable use of marine resources. Prior to utilization, the levels of undesirable substances need to be examined, and earlier studies on mesopelagic species have reported on total arsenic (As) content. However, the total As content does not give a complete basis for risk assessment since As can occur in different chemical species with varying toxicity. In this work, As speciation was conducted in single-species samples of the five most abundant mesopelagic organisms in Norwegian fjords. In addition, As species were studied in mesopelagic mixed biomass and in the resulting oil and meal feed ingredients after lab-scale feed processing. Water-soluble As species were determined based on ion-exchange high-performance liquid chromatography coupled to inductively coupled plasma mass spectrometry (HPLC-ICP-MS). This was supplemented by extracting arsenolipids (AsLipids) and determining total As in this fraction. The non-toxic arsenobetaine (AB) was the dominant form in mesopelagic crustaceans and fish species, accounting for approximately 70% and 50% of total As, respectively. Other water-soluble species were present in minor fractions, including carcinogenic inorganic As, which, in most samples, was below limit of quantification. The fish species had a higher proportion of AsLipids, approximately 35% of total As, compared to crustaceans which contained 20% on average. The feed processing simulation revealed generally low levels of water-soluble As species besides AB, but considerable fractions of potentially toxic AsLipids were found in the biomass, and transferred to the mesopelagic meal and oil. This study is the first to report occurrence data of at least 12 As species in mesopelagic organisms, thereby providing valuable information for future risk assessments on the feasibility of harnessing mesopelagic biomass as feed ingredients. Graphical abstract: Image 1 Highlights: Up to 12 arsenic species were detected in mesopelagic samples. Arsenobetaine comprised 70% and 50% of total As in crustaceans and fish, respectively. Mesopelagic mixed biomass comprised mainly of arsenobetaine and arsenolipids. Arsenolipids were transferred to meal and up-concentrated in oil when processed. Inorganic arsenic was <0.007 mg/kg ww in most samples.